1994
DOI: 10.1080/00288233.1994.9513036
|View full text |Cite
|
Sign up to set email alerts
|

Autumn establishment of three New Zealand cultivars of tall fescue(Festuca arundinaceaSchreb.) for seed production

Abstract: Three New Zealand cultivars of tall fescue (Festuca arundinacea Schreb.), Grasslands Roa, Grasslands Garland, and Grasslands Advance, were autumn-sown on three sowing dates 3 weeks apart (4 March, 25 March, and 15 April 1991). The turf-type cultivar Grasslands Garland produced significantly (P < 0.05) more seed in the first summer from autumn sowings than the two pasturetype cultivars, Grasslands Roa and Grasslands Advance. Time of sowing in the autumn was found to be critical as a delay of only 3 weeks in sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…These factors have a particularly dominant influence on seed yield in the first production year and the effects persist for several successive seed crops. The results confirm the importance of an adequate density of tillers prior to winter for seed yield of tall fescue (Robson 1968;Hare 1992Hare , 1993Hare , 1994. The pattern of response of seed yield to plant density was similar for each of the three row spacings in this study.…”
Section: Discussionsupporting
confidence: 74%
“…These factors have a particularly dominant influence on seed yield in the first production year and the effects persist for several successive seed crops. The results confirm the importance of an adequate density of tillers prior to winter for seed yield of tall fescue (Robson 1968;Hare 1992Hare , 1993Hare , 1994. The pattern of response of seed yield to plant density was similar for each of the three row spacings in this study.…”
Section: Discussionsupporting
confidence: 74%
“…The dependence of tall fescue seed yield on the number of panicles m -2 has been well documented in New Zealand by Hare (1992Hare ( , 1993Hare ( , 1994 who also found that fertile tiller density was particularly important for the first seed crop (Hare 1994). Based on these studies, and on others from the USA (Watson and Watson 1982;Albeke et al 1983;Chastain and Grabe 1989) and Japan (Suzuki 1989), which each reported a maximum density of reproductive tillers of 400 to 600 m -2 , Hare (1993) agreed with the earlier interpretation of Robson (1968) that the density of reproductive tillers in tall fescue may be limited genetically, and that insufficient nutrient resources may preclude the attainment of reproductive tiller densities as high as 1000 to 2000 m -2 .…”
Section: Discussionmentioning
confidence: 99%